Effect of Arrabideae chica (crajiru) extract in a model of induced experimental colitis in rats - Mayara de Araujo Silva, Evelynne; Medeiros Azevedo, Ítalo; Araújo Filho, Irami; Cunha Medeiros, Aldo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2021)
Objective: This study aimed to investigate the effect of A. chica extract on the evolution of experimental rectocolitis in rats, and the expression of the pro-inflammatory cytokines TNF-a, IL-1? and IL-6 in colonic tissue. Methods: Wistar rats weighing 275±23g were distributed into 4 groups of 6 animals each. Rectocolitis was induced in rats by rectal administration of trinitrobenzene sulfonic acid (TNBS). Seventy-two hours after TNBS injection, animals were treated daily for 6 days. Groups: 1. Normal control group without induction of rectocolitis. Received 0.9% saline injection v.o. by gavage during treatment. 2. TNBS rectocolitis group, treated with normal saline (SN) by gavage (TNBS+SN); 3. TNBS rectocolitis group treated with A. chica extract (ACE), receiving a daily dose of 300 mg of A. chica extract by gavage (TNBS+ACE);4. TNBS rectocolitis group treated with mesalazine, receiving a daily dose of 100 mg/kg of mesalazine orally (TNBS+MEZ). Macroscopic examination of the colon and dosing of TNF-?, IL-1? and IL-6 in colon tissue were performed. Results: There was a reduction in weight in animals treated only with TNBS+NS. No difference in weight was observed comparing the animals treated with ACE and MEZ. In the control group no mucosal ulcers or edema of the colon wall were observed. Several mucosal ulcers, edema and hyperemia occurred in the colon of rats in the TNBS+SN group. In two of the animals in this group there was colon perforation, tamponated by omentum. A reduction of mucosal ulcers number in the TNBS+ACE (crajiru) group was seen, compared to the TNBS+SN and TNBS+MEZ group. There was a significant reduction of TNF-?, IL-1? and IL-6 in the colon tissue of animals treated with crajiru extract, TCBS+ACE group, when compared to the control group (p<0.001), TNBS+SN group, and TNBS+MEZ groups (p<0.001). Conclusion: This is the first study to show that A. chica extract positively influences the treatment of TNBS/induced rectocolitis through its antiinflamatory activity. More comprehensive studies are needed to understand the underlying mechanisms.